Literary Competence Improvement on Listening Short Story using Pakem Strategy With TGT (Team Games Tournament ) Method - Tutik Yuliati (Pioneer: Journal of Language and Literature, 2018)
Literature teaching at school is aied to give the basic of literary awareness to the students, so they can learn to love and appreciate literature well based on the literary rules they have got. One example of literary works is shortstory.we can teach students short story in listening class. However, their literary competence is found out to be low. Therefore, the teacher proposed TGT method to improve students’ literary competence. The results reveals that working activities during listening show students’ positive appreciation to literature. However, the teacher should have more give attention to the aspects of short story.